The effect of education and work environment on employee performance mediated by work motivation - Desi Vaulina (Institute of Computer Science (IOCS), 2023)
The purpose of this study was to determine the effect of Education, Work Environment, Work Motivation, Employee Performance. The population of this study were all employees of PT. Inti Sela data was collected by 65 respondents and processed with IBM AMOS version 23 software. Based on the results of the study, empirical facts were obtained in the form of: Education has a positive effect on Work Motivation, Work Environment has a positive effect on Work Motivation, Work Motivation has a positive effect on Employee Performance, Education has a positive effect on Employee Performance, Work Environment has a positive effect on Employee Performance, Education has no positive effect on Employee Performance which is mediated by Work Motivation. There is no effect of Work Motivation on Employee Performance and the effect is moderate1 (X1*Z) Therefore, work incentives are unlikely to act as a moderating factor (not a moderating variable). The correlation between Education and Employee Performance is not influenced by Work Motivation, Work Motivation acts as a mediating factor between the Work Environment and Employee Performance. Work Motivation Has Moderate Effect on Employee Performance (X2*Z) The linkage between Work Environment and Employee Performance is strengthened by Work Motivation which indicates that it is possible to act as a moderating element